Assistance for Posyandu Members "Kasih Ibu" Penanggungan Village, Klojen District, Malang City with Training in Making Handicrafts from Plastic Waste Beverage Sachets - Kurnia Isnuwardiati; Dyah Setyawati; Lilik Kustiani; Diah Widiawati (Jurnal Pengabdian Masyarakat Bestari, 2023)
Until now, the garbage is still a serious problem in the surrounding environment, both in the wider environment and the household community. Public awareness is considered very necessary in waste management efforts, not least for mothers of Posyandu Kasih Ibu members. Is waste derived from sachet beverage plastic waste which is currently very popular. The efforts to recycle waste into a product are expected not only to contribute to reducing waste but also to become a home product with high economic value. Participatory Rural Appraisal (PRA) is used as an approach method to invite the community to actively participate in the development of an activity. In this activity, the community that is the target of this program is the mothers of the cadre of Posyandu Kasih Ibu members, they are equipped with knowledge first about the importance of participation in waste management and then provide training in making handcrafts from the remaining waste of sachet drink packs. Based on the results of these activities, the members of the Kasih Ibu Posyandu cadre have been able to produce several handcraft motifs derived from sachet beverage wrapper waste.